Pengaruh Pemberian Ekstrak Etanol Rimpang Lengkuas (Alpinia galanga) terhadap Gambaran Histopatologi Testis Mencit (Mus musculus L.) jantan yang Diinduksi Monosodium Glutamat - Annisa Shafira Pramono; Muhartono; Rizki Hanriko; Eca Cania (CV. Jasa Sukses Abadi, 2020)
Monosodium Glutamate (MSG) may form free radicals that cause damages to the organs of the body, one of which is the male reproductive organs, i.e. testes. Galangal rhizome is one of the natural ingredients with antioxidant content that can neutralize free radicals. The purpose of this research was to determine the effect of ethanol extract of galangal rhizome on testicular histopathology of MSG-induced male mice. The design of this research was experimental research with 5 treatment groups, each group consisted of 5 mice (Mus musculus L.) DDY strain. Group K (-) was not treated; k (+) was provided with 4 mg/ grBB MSG; P1 was provided with 4 mg/ grBB MSG + 14 mg/ 20 grBB ethanol extract of galangal rhizome; P2 was provided with 4 mg/ grBB MSG + 28 mg/ 20 grBB ethanol extract of galangal rhizome; P3 was provided with 4 mg/ grBB MSG + 56 mg/ 20 grBB ethanol extract of galangal rhizome. Assessment used Johnsen score in group K(-) was 48,4, K(+) was 47,4, P1 was 47,4, P2 was 47,4, and P3 was 48. Kruskal-Wallis test result was p=0,085 (p>0,05). The conclusion was that ethanol extract of galangal rhizome did not effect significantly (p>0,05) on the testicular histopathology of monosodium glutamate-induced mice.